Pemikiran Gus Dur dalam Kehidupan Pluralitas Masyarakat Indonesia - Ahmad Zainuri; Luqman Al-Hakim (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2021)
Abstract: Abdurrahman Wahid or often known as Gus Dur, is a nationalist thinker, writer and kyai in Indonesia. His ideas and thoughts have given a glimmer of light to some Indonesian Muslims about the importance of respecting and living tolerance. In his intellectual perspective, the basic foundation for building a pluralistic Indonesia is based on a national cultural and ideological foundation, none other than Pancasila. Because these two foundations build on the history of nationalism, both personally and collectively. Grounding Islam as one of Gus Dur's noble nawacitas to unite the values ​​and norms of religious spirituality, namely the beauty of religion. In this article the author uses a biographical approach. The concept of historical writing: data, facts, sources and methods. With several approaches, concepts and methodologies of historical research, this writing uses a literature review or literature study with several primary and secondary historical sources from Gus Dur's works as well as several other writers who discuss Gus Dur and scientific journals. Gus Dur's thinking is a thought based on pluralism-humanism, Pancasila, Islamic indigenization and Islamic cosmopolitanism.